2022
DOI: 10.3390/molecules27154895
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant, Antibacterial, and Antibiofilm Activities of Backhousia citriodora Essential Oil

Abstract: The essential oil of Backhousia citriodora, commonly known as lemon myrtle oil, possesses various beneficial properties due to its richness in bioactive compounds. This study aimed to characterize the chemical profile of the essential oil isolated from leaves of Backhousia citriodora (BCEO) and its biological properties, including antioxidant, antibacterial, and antibiofilm activities. Using gas chromatography–mass spectrometry, 21 compounds were identified in BCEO, representing 98.50% of the total oil content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 108 publications
0
16
0
Order By: Relevance
“…Furthermore, our findings were in agreement with studies in which the antioxidant activity could be attributed to the major monoterpenoids such as menthone (29.4%), carvone (70.25%), and Levomenthol (43.32%) [ 45 , 68 , 69 ]. Several studies have shown that enhanced antioxidant properties are found in EOs [ 70 ]. Hence, the chemical compounds of EO from M. piperita might work individually or synergistically as natural antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our findings were in agreement with studies in which the antioxidant activity could be attributed to the major monoterpenoids such as menthone (29.4%), carvone (70.25%), and Levomenthol (43.32%) [ 45 , 68 , 69 ]. Several studies have shown that enhanced antioxidant properties are found in EOs [ 70 ]. Hence, the chemical compounds of EO from M. piperita might work individually or synergistically as natural antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…The citral (60.5–88.7%) was the main component in the EOCC, equal to or better than the citral-rich plants, including Backhousia citriodra (85–95%) [ 4 , 26 ]; Litsea cubeba (70–90%) [ 42 ]; Cymbopogan flexuosus (65–85%) [ 43 ]; Ocimum gratissimum (65–75%) [ 44 ]; Lippia citriodor (30–60%) [ 1 , 45 ]; Citrus aurantium bigarade (25–30%) [ 46 ]. The citral chemotype C. camphora and C. bodinieri , as the evergreen tree, had more advantages for extracting citral in terms of biomass, oil yield of essential oil and citral content; moreover, their tending and harvesting can be mechanized.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidation of natural plant essential oils is very important for their application in the fields of medicine, food and spices, which overcome the deleterious effect of chemically synthesized antioxidants. The 2,2-diphenyl-1 picrylhydrazyl (DPPH) free radical scavenging test, scavenging 2,2′-azinobis(3-ethylbenzo thiazoline-6-sulfonic acid) diammonium salt radical (ABTS) and the ability of Ferric reducing antioxidant power (FRAP) are the most common methods used to evaluate the antioxidant activity of compounds, and various phytoconstituents and their potential antioxidant activities have been reported previously [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. In terms of the C. camphora’s antioxidant activities, linalool, eucalyptol, camphor and borneol chemotypes with strong scavenging activity against 2,2-diphenyl-1 picrylhydrazyl (DPPH) were proved [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these oils appear to be effective at inactivating many microbes without causing resistance to antimicrobials [ 147 ]. Its low toxicity to mammalian cells, quick environmental decomposition, and the availability of diversified essential oils make them potential antibiofilm agents [ 148 , 149 , 150 ]. Some of the recently reported essential oils and their antibiofilm activities against different pathogenic microbial strains are discussed below and summarized in Table 4 .…”
Section: Bacterial Biofilmsmentioning
confidence: 99%